Depression, Stress and Anxiety among Residents of Nepal during COVID-19 Lockdown - Basnet, Sandhya; Bhandari, Bhawana; Gaire, Bipula; Sharma, Pujan; Shrestha, Rajendra Man (Journal of Advanced Academic Research, 2021)
Covid-19 illness is a pandemic infectious disease caused by a new coronavirus that originated in Wuhan, China. Nepal being a landlocked underdeveloped country is particularly vulnerable to the pandemic. Similarly, the dread of contracting the coronavirus is making people concerned about a global pandemic. It is vital to determine the impact of viral outbursts on mental health. Hence, this study aims to identify level of depression, stress and anxiety during lockdown among Nepalese residents. Cross-section web-based research design was undertaken at Bagmati province, Gandaki province and Lumbini province with four hundred twenty-two (n=422) (n=422) Nepalese residents by using a multistage proportionate stratified random sampling method. The Dass-21 tool was used to assess level of depression, stress and anxiety. Among 422 respondents only 5.9% had extremely severe level of anxiety, whereas 14.5% were moderately depressed, 77.5% did not have any stress during lockdown. There was statistically significant difference between depression and age (p=0.016), depression and sex (p=0.023). Also, there was a significant difference between stress and age (p=0.023), sex (p=0.0263) and education level (p=0.049).It is concluded that more than two-third of the respondentsere found to be in normal ranges for depression, stress and anxiety. Less than one-fourth of respondents had moderate to severe level of anxiety and depression.